Preparation method of hydrogel hemostatic patch with underwater adhesion

By introducing phenylborate bonds into hydrogel patches, the problem of unstable adhesion of existing hydrogel patches in water-rich environments is solved, and fast and strong underwater tissue adhesion and releasable performance is achieved, which is suitable for hemostasis and wound treatment.

CN119770707AActive Publication Date: 2025-04-08BEIJING JURENTON-MED TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510272884.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

Existing hydrogel patches cannot quickly remove interface water in water-rich environments, resulting in slow and unstable adhesion activation, limiting their application in surgical and underwater injuries.

Method used

HPAA hydrogel precursor solution is prepared by mixing antho-aminophenylboric acid modified hyaluronic acid, acetylated β-cyclodextrin, acrylic acid, α-ketoglutaric acid and water, and forming a hydrogel patch under ultraviolet light, using the phenylborate bond to improve adhesion speed and performance.

Benefits of technology

It achieves rapid adhesion to the wet tissue surface within 1-2 seconds, exhibits strong adhesion strength up to 163.2kPa, and has releasable properties, suitable as hemostasis and wound treatment materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770707A_ABST
    Figure CN119770707A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a hydrogel hemostatic patch with underwater adhesion. The preparation method of the patch comprises the following steps: mixing o-aminophenylboronic acid modified hyaluronic acid, acetylated beta-cyclodextrin, acrylic acid, alpha-ketoglutaric acid and water to prepare an HPAA hydrogel precursor solution; and adding the hydrogel precursor solution into a mold, and performing ultraviolet irradiation to obtain the hydrogel, wherein the ratio of the o-aminophenylboronic acid modified hyaluronic acid to the acetylated beta-cyclodextrin to the acrylic acid to the alpha-ketoglutaric acid to the water in parts by weight is (13-17): (9-11): (140-160): (0.5-1.5): (300-350). The invention aims to provide a preparation method of a hydrogel hemostatic patch with underwater adhesion. The hydrogel hemostatic patch is used for rapid and strong underwater tissue adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hemostatic patches, and in particular to a method for preparing a hydrogel hemostatic patch with underwater adhesion. Background Art

[0002] The leading cause of death during surgery and trauma is uncontrolled bleeding, which accounts for more than 30% of trauma-related deaths. When the body's natural clotting process cannot control rapid bleeding, the timely use of hemostatic materials is essential to quickly stop bleeding and save lives. Traditional hemostatic materials include dry sponges, gauze, bandages or tourniquets, and then the wound is closed with sutures or staples. However, combining these dry hemostatic materials with sutures or staples has some disadvantages, including time-consuming, complicated operation and causing additional tissue damage. These disadvantages reduce the survival rate of patients in emergency situations and significantly limit the efficiency of bleeding treatment.

[0003] Hydrogel patches can provide strong wet tissue adhesion, biomimetic mechanical strength and elasticity. The prior art discloses a polyacrylic acid-related dry cross-linked magnetic tape, which removes the interfacial water of the tissue through pressure and the mechanical action of its own swelling, so that the carboxyl groups on the surface of the PAA can form strong ionic crosslinks with the amine groups in the tissue within 5 seconds, and then the NHS ester groups and the primary amine groups of the tissue gradually form covalent crosslinks within a few minutes. In recent years, researchers have also incorporated various interactions into hydrogel patches based on the adhesion mechanism of PAA. By adding charge interactions, π-π interactions, cation-π interactions, hydrogen bonds and hydrophobic effects to enhance the crosslinking of hydrogel patches, significant progress has been made in improving toughness, controlling swelling, reducing potential inflammation, and improving biocompatibility. These improvements have promoted better clinical applications of PAA-related hydrogel patches.

[0004] However, in a watery environment, most of the current hydrogel patches cannot quickly remove the interfacial water in contact with the patch, resulting in slow adhesion activation and unstable adhesion performance. This is still a challenge that limits the use of adhesive patches in real-life scenarios. In real surgical operations or underwater injuries, the injured area is often immersed in water or body fluids, which produces not only a wet interface, but also a highly hydrated tissue interface. Most PAA patches in the prior art discharge the wet interfacial water layer by pressure at a speed of more than 5 seconds, and the drainage effect in underwater environments is poor. In addition, with limited operating space and manpower, it is difficult to apply sufficient external pressure to these patches reported in the past. That is, if the patch cannot quickly remove the interfacial water between tissues, it will lose adhesion due to surface hydration and it is impossible to adhere completely, which greatly limits the success rate of most existing hemostatic patches.

[0005] At present, most existing wet tissue hydrogel patches rely mainly on physical compression and expansion to remove and absorb interfacial water during the adhesion process. In a highly hydrated environment, this method is usually slow and inefficient. In view of this, the present invention provides a method for preparing a hydrogel hemostatic patch with underwater adhesion properties. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a hydrogel hemostatic patch with underwater adhesion for rapid and strong underwater tissue adhesion.

[0007] The invention provides a method for preparing a hydrogel hemostatic patch with underwater adhesion. The method comprises: mixing hyaluronic acid modified by o-aminophenylboronic acid, acetylated beta-cyclodextrin, acrylic acid, alpha-ketoglutaric acid and water to prepare a HPAA hydrogel precursor solution; and adding the hydrogel precursor solution into a mold and irradiating the mold with ultraviolet light to obtain the hydrogel hemostatic patch.

[0008] Furthermore, the weight ratio of the o-aminophenylboronic acid modified hyaluronic acid, acetylated β-cyclodextrin, acrylic acid, α-ketoglutaric acid and water is (13-17): (9-11): (140-160): (0.5-1.5): (300-350).

[0009] Furthermore, the weight ratio of the o-aminophenylboronic acid-modified hyaluronic acid, acetylated β-cyclodextrin, acrylic acid, α-ketoglutaric acid and water is 15:10:150:1:324.

[0010] Furthermore, the wavelength of the ultraviolet light is 360-370 nm, and the irradiation time is 9-11 min.

[0011] Furthermore, the preparation method of the o-aminophenylboronic acid modified hyaluronic acid includes: dissolving hyaluronic acid in deionized water, adding N-hydroxysuccinimide and 1-(3-dimethylpropyl)-3-ethylcarbodiimide in sequence for mixed reaction, then adding 2-aminophenylborate hydrochloride to obtain a mixed solution, adjusting the pH of the mixed solution to 4-5 for reaction, then adjusting the pH to 7.5-8.5 to stop the reaction, then dialyzing, freezing and freezing, and then placing in a freeze dryer for freeze drying to obtain the obtained solution.

[0012] Furthermore, the weight ratio of the hyaluronic acid, deionized water, N-hydroxysuccinimide, 1-(3-dimethylpropyl)-3-ethylcarbodiimide and 2-aminophenylborate hydrochloride is (8-12):(180-220):(6-8):(10-14):(4-6).

[0013] Furthermore, the pH is adjusted by adding 0.8-1.2 M sodium hydroxide aqueous solution. When the pH is 4-5, the reaction needs to be stirred at room temperature for 11-13 hours.

[0014] Furthermore, the dialysis step comprises: using a dialysis bag with a molecular weight cutoff MWCO: 3000-4000Da, dialysis with an aqueous solution containing a mass concentration of 0.8-1% sodium chloride for 46-50 hours, and then further dialysis with deionized water for 22-26 hours.

[0015] Furthermore, the preparation method of the acetylated β-cyclodextrin includes: dissolving β-cyclodextrin and triethylamine in anhydrous N,N-dimethylformamide, stirring and reacting at 250-350 r / min for 0.8-1.2 hours at 0-1°C and under nitrogen protection, then adding acryloyl chloride and continuing to stir and react at 250-350 r / min for 10-14 hours at room temperature, filtering and washing the precipitate, redissolving it in deionized water, freezing it, and then putting it into a freeze dryer for freeze drying to obtain a sponge-like product.

[0016] Furthermore, the weight ratio of the β-cyclodextrin, triethylamine, anhydrous N,N-dimethylformamide and acryloyl chloride is (8-12): (6-8): (55-66): (4-8).

[0017] Furthermore, the precipitate is washed by ethyl acetate precipitation, the amount of ethyl acetate added is more than 50 times the volume of the precipitate, and the precipitate is filtered and washed more than three times.

[0018] The beneficial effects of the present invention are: The present invention proposes a novel HPAA hydrogel patch. After the patch contacts the tissue surface, the phenyl borate bonds on the surface will quickly break and absorb water, thereby significantly enhancing the water absorption, improving the adhesion speed and performance. By introducing the phenyl borate bonds into the polyacrylic acid system, the patch can quickly adhere to the wet tissue surface within 1-2 seconds and show a strong adhesion strength of up to 163.2 kPa. In addition, the phenyl borate bonds also give the patch a releasable property, and the patch can be easily detached from the adhered tissue using a glucose solution. At the same time, the mechanical properties of the patch can be optimized by adjusting the ratio of covalent and non-covalent interactions, thereby achieving high strain (2296%) and high toughness (82 kPa). Both in vivo and in vitro experimental results show that the patch performs well in rapid organ hemostasis and seamless suture. Therefore, the HPAA patch shows broad biomedical application prospects in the preparation of hemostasis and wound treatment materials with its excellent underwater adhesion, mild on-demand peeling performance, adjustable mechanical strength and good biocompatibility.

[0019] In addition, the dynamic bonding properties of the phenylboronate bonds enable gentle and painless on-demand detachment of the patch by glucose solution, effectively reducing potential inflammatory responses associated with slow PAA degradation. In addition, the HPAA1 patch uses a multi-network cross-linking system that combines dynamic bonds (such as phenylboronate bonds and hydrogen bonds) with a small number of non-dynamic bonds (such as covalent CC bonds), providing easily adjustable toughness and strength to adapt to the softness and hardness of biological tissues. Preliminary in vitro and in vivo animal experiments have verified the potential of the HPAA1 patch in a variety of medical applications, including rapid hemostasis and sutureless wound closure.

[0020] The present invention also uses HA-PBA, Ac-βCD and AA as dynamic physical cross-linking agents, and uses α-ketoglutaric acid as an initiator to initiate polymerization under 365nm ultraviolet light to successfully prepare an HPAA1 hydrogel patch. The patch has a stable formula, a simple preparation method, and significant economic value. HPAA1 hydrogel has shown a wide range of biomedical application potential in the preparation of hemostatic and wound treatment patches due to its excellent underwater adhesion, mild on-demand peeling performance, adjustable mechanical strength, and good biocompatibility. At the same time, the introduction of phenylboronic acid bonds into the PAA adhesion system can quickly remove interfacial water, thereby improving the underwater adhesion speed and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 Schematic diagram of the formation, adhesion and application of HPAA hydrogel; 1A is a hydrogel network diagram, 1B is an adhesion principle diagram, 1C is a glucose solution release principle diagram, and 1D is an HPAA patch application prospect diagram.

[0023] Figure 2 Schematic diagram of the synthesis of HAPBA and AC-β-CD; wherein 2A is the synthesis reaction formula of HAPBA, 2B is the synthesis reaction formula of AC-β-CD, 2C is the NMR result diagram of HA and HA-PBA, and 2D is the NMR result diagram of β-CD and AC-β-CD.

[0024] Figure 3Characterization diagrams of HAAA and HPAA hydrogels; 3A is a Fourier infrared image, 3B is a swelling schematic diagram, 3C is a swelling statistical diagram, 3D is a statistical diagram of the elastic modulus (G') and viscous modulus (G") at a fixed frequency in the strain range of 0.1%~10000%, 3E is a dynamic frequency scanning measurement statistical diagram at a constant strain of 1% and a frequency between 0.1 and 100 Hz, 3F is a scanning electron microscope (SEM) image, and 3G is a pore diameter statistical diagram.

[0025] Figure 4 The figure shows that HPAA1 has good self-healing ability; among them, 4A is a statistical diagram of the step oscillation test under continuous alternating strain scanning (1% to 10000%), and 4B to 4D are schematic diagrams showing the self-healing ability.

[0026] Figure 5 5A is a diagram of the tensile properties of HPAA and HAAA hydrogels; 5B is a diagram of the fracture toughness experiment, 5C is a diagram showing the application of an underwater bandage, and 5D is a diagram showing the adhesion of the skin surface of a bent joint.

[0027] Figure 6 Figures 6A to 6F are diagrams of adhesion and separation of HAAA and HPAA hydrogels underwater; among them, 6A to 6F are diagrams of wet pig skin adhesion performance, 6G is a demonstration diagram of underwater pig skin adhesion, 6H is a diagram of underwater adhesion principle, and 6I is a representative diagram of on-demand painless and noninvasive separation in glucose solution.

[0028] Figure 7 Figures 7A and 7B show the adhesion performance of HAAA and HPAA hydrogels to various materials and organs; Figure 7A is a schematic diagram of the adhesion of iron, rubber, plastic, glass, and polytetrafluoroethylene; Figure 7B is a schematic diagram of the adhesion of wet organ tissues (heart, liver, spleen, lung, and kidney); and Figures 7C to 7H are wet organ adhesion curves and statistical graphs.

[0029] Figure 8 The biocompatibility and biodegradability diagram of the HPAA hydrogel patch; wherein, 8A is a schematic diagram of co-culture, 8B is a live-dead staining diagram of co-cultured cells, 8C to 8E are in vivo and in vitro degradation and statistical diagrams, and 8F is an in vivo biosafety test diagram.

[0030] Fig. 9 Figure 9 is a diagram of the application of HPAA patch in wound closure of a rat full-thickness skin incision model; wherein 9A is a schematic diagram of modeling, and 9B is a schematic diagram of skin wound healing.

[0031] Fig.10 These are histological evaluation images of wound healing after HPAA patch treatment; 10A is HE and Masson staining images, 10B and 10C are statistical images of related indicators, 10D is immunofluorescence staining image, and 10E and 10F are statistical images of related indicators.

[0032] Fig.11 11A is a schematic diagram of hemostasis of liver injury, 11B is a schematic diagram of the operation flow of hemostasis of liver injury, 11C and 11D are a diagram of liver bleeding volume and statistics, 11E is a schematic diagram of HE staining of liver tissue after hemostasis, 11F is a schematic diagram of tail hemostasis, 11G and 11H are schematic diagrams and statistics of tail bleeding volume, 11I is a schematic diagram of hemostasis of heart injury, and 11J is a schematic diagram of the operation flow of hemostasis of heart injury.

[0033] Fig.12 Schematic diagram of potential applications of HPAA patch; among them, 12A is a schematic diagram of lung injury repair and a schematic diagram of experimental results, 12B is a schematic diagram of heart injury repair and a schematic diagram of experimental results, and 12C is a schematic diagram of gastric injury repair and a schematic diagram of experimental results. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that hyaluronic acid (HA) (Mw = 35 kDa) in the present invention was purchased from Yuanye (Shanghai, China); N-hydroxysuccinimide (NHS), 1-(3-dimethylpropyl)-3-ethylcarbodiimide (EDC), acrylic acid (AA) and acryloyl chloride were all purchased from Aladdin (Shanghai, China); 2-aminophenylborate hydrochloride (PBA) was purchased from Leyan (Shanghai, China); β-cyclodextrin (β-CD) was purchased from Maclean (Shanghai, China); α-ketoglutaric acid was purchased from Sigma-Aldrich.

[0036] Example See also Figures 1 to 3 , this embodiment provides a method for preparing a hydrogel patch: Preparation of hyaluronic acid modified with o-aminophenylboronic acid (HA-PBA): first, 10 parts by weight of HA was dissolved in 200 parts by weight of deionized water, and then 7 parts by weight of N-hydroxysuccinimide (NHS) and 12 parts by weight of 1-(3-dimethylpropyl)-3-ethylcarbodiimide (EDC) were added in sequence, and the mixture was mixed and reacted for 1 hour; then, 5 parts by weight of PBA was added to the solution, and the pH was adjusted to 4.5 using a 1M sodium hydroxide (NaOH) solution, and the mixture was stirred at 300 r / min for 12 hours at room temperature, and then the pH was adjusted to 8 using a 1M concentration of NaOH, and the mixture was placed in a dialysis bag with a molecular weight cutoff MWCO: 3500Da, and dialyzed with a 0.9% sodium chloride aqueous solution for 48 hours, and then further dialyzed with deionized water for 24 hours; The modification rate of HA-PBA after dialysis and freeze-drying was 30% as determined by 1HNMR. Figure 2 2A and 2C in.

[0037] Preparation of acetylated β-cyclodextrin (AC-β-CD): 10 parts by weight of β-CD and 7 parts by weight of triethylamine were dissolved in 60 parts by weight of anhydrous DMF, and then stirred at 0°C under nitrogen protection for 1 hour, then 5 parts by weight or 7 parts by weight of acryloyl chloride were added to the solution, and stirred at room temperature for 12 hours. The liquid was filtered through a sand core funnel, precipitated with ethyl acetate more than 50 times the volume of the precipitation and washed more than 3 times; then, the solid was redissolved in 10 times the volume of deionized water, and freeze-dried to obtain low-modification AC-β-CD (Ac-β-CD-low) and high-modification AC-β-CD (Ac-β-CD-high). The modification rates were 150% and 200%, respectively, as determined by 1HNMR. Please refer to Figure 2 2B and 2D in .

[0038] HA-PBA and AC-β-CD synthesized as described above, together with acrylic acid (AA), α-ketoglutaric acid, and water, were used as the precursor solution for preparing HPAA hydrogel.

[0039] The precursor solution of the HAAA patch used as a control for the HPAA patch contained HA, Ac-β-CD, acrylic acid (AA), α-ketoglutaric acid, and water (without the boronate bond).

[0040] The detailed compositions of all hydrogels are listed in Table 1, and all raw materials are expressed in parts by weight.

[0041] The above precursor solution was added into the polytetrafluoroethylene patch mold according to the proportion in the table, and after irradiation with 365nm ultraviolet light for 10 minutes, the formed and dried HPAA patch and HAAA patch were obtained.

[0042] Compared with the other three groups, the HPAA1 patch has a stable formulation and suitable underwater adhesion and mechanical properties. On the one hand, HAAA1 is used as a control to compare the role of the phenylboronic acid ester bond in HPAA1; on the other hand, HPAA2 is also used as a control to prove that HPAA1 has a more suitable Ac-β-CD substitution degree (i.e., C=C double bond concentration).

[0043] Table 1 Formula ingredients After testing, Fourier transform infrared (FTIR) spectroscopy confirmed the successful synthesis of HPAA hydrogel and the existence of phenyl borate ester bonds and hydrogen bonds therein, such as Figure 3 As shown in 3A.

[0044] Test Example 1 Characterization of hydrogels: The equilibrium swelling ratio (ESR) was determined by the weighing method. After UV irradiation, the hydrogel was immersed in pure water and then placed in an incubator at 37 °C. The hydrogel samples were weighed every 1 hour until the swelling equilibrium was reached.

[0045] The calculation formula of ESR is as follows: ESR=(W t −W d ) / W d ×100%.

[0046] Among them, W t is the weight of the hydrogel in the swelling equilibrium state, W d is the initial weight of the hydrogel.

[0047] After immersion for 5 h, the swelling degrees of HAAA1 and HPAA1 were approximately 25 and 21 times, respectively, while the swelling degrees of HAAA2 and HPAA2 were approximately 7 and 5 times, respectively. Throughout the swelling process, the swelling degree of HAAA1 and HPAA1 patches was faster than that of HAAA2 and HPAA2, because the latter had more covalent cross-links, making the structure more compact and limiting the water absorption capacity. In addition, the HPAA1 patch also showed the fastest swelling trend in the initial stage, because the phenyl boronate bond increased the water absorption rate, such as Figure 3 As shown in 3B and 3C.

[0048] Rheological measurements were performed using a Kinexus rheometer equipped with 25 mm diameter parallel plates. Dynamic amplitude sweep tests were used to determine the linear viscoelastic region and to record the elastic modulus (G') and viscous modulus (G") at a fixed frequency in the strain range of 0.1% to 10,000%. Dynamic frequency sweep measurements were performed at a constant strain of 1% and frequencies between 0.1 and 100 Hz to further characterize the rheological properties of the hydrogels.

[0049] The strain amplitude sweep test showed that the gel point modulus of HPAA hydrogels containing phenylboronic acid ester bonds was significantly higher than that of HAAA hydrogels, and the G' and G" moduli of HPAA2 hydrogels containing highly substituted Ac-β-CD were higher. Figure 3 3D and 3E in.

[0050] The morphology of the hydrogel was analyzed by scanning electron microscopy (SEM). After rapid freezing in liquid nitrogen for 30 seconds, the sample stage with the attached sample was transferred to the sample preparation room, sublimated at -90°C for 10 minutes, gold plated at a current of 10 mA for 60 seconds, and then sent to the scanning electron microscope sample room for observation. Scanning electron microscopy imaging was performed using a FEI Quanta 450 instrument at an accelerating voltage of 3.0 kV, and the pore size of each sample was calculated using the ImageJ tool.

[0051] The experimental results show that the HPAA2 hydrogels using higher degree of substitution Ac-β-CD exhibited a significantly dense structure and smaller pore size, which is due to the more covalent cross-linking of Ac-β-CD groups in the poly (AA / Ac-β-CD) chain, which is related to its smaller absorption rate and lower swelling rate, such as Figure 3 As shown in Figures 3F and 3G.

[0052] Test Example 2 Mechanical self-healing properties of HPAA: HPAA1 hydrogel diluted 1.3 times was subjected to a step oscillation test for 5 consecutive cycles under a continuous alternating strain sweep (1% to 10000%) of the rheometer. Figure 4 4A in Figure 4. To observe the self-healing ability of HPAA1, two HPAA patches (30×15×2 mm) were cut into two pieces, one of which was blue and the other red. The freshly cut surfaces of different colors were then kept in close contact with the clamp at room temperature. After about 60 min, the edge of the self-healing hydrogel was clamped with tweezers, and it was observed that the HPAA1 hydrogel had excellent self-healing ability, as shown in Figure 4A. Figure 4 As shown in 4B to 4D in FIG.

[0053] Test Example 3 Mechanical properties: The mechanical properties of the materials were evaluated at room temperature using a universal testing machine (CMT-1104, SUST, Zhuhai, China). Four specimens (30 × 15 × 2 mm) were tested at a rate of 100 mm / min for each material. Figure 5 5A in. To determine fracture toughness using a stress-strain curve, record the force and then use the formula: Calculate where F is the platform force in the peel test, and W and L are the length and width of the sample, respectively.

[0054] The tensile stress-strain curves show that the tensile strengths of HAAA1, HAAA2, HPAA1 and HPAA2 hydrogels are 32 kPa, 54 kPa, 45 Pa and 107 kPa, respectively, and the fracture strains are 1812%, 482%, 2334% and 755%, respectively. Please refer to Figure 5 5B in.

[0055] Compared with the control group, the HPAA1 hydrogel has a better tensile elongation, which is due to the dynamic non-covalent bond characteristics of the phenylboronic acid ester bond, which provides the hydrogel with better extensibility.

[0056] The data in Table 1 also show that the HPAA1 prepared in the present invention exhibits the highest tensile properties under moderate intermolecular forces by adjusting the ratio of covalent bonds and phenylboronic acid ester bonds. In addition, in order to confirm the underwater tensile properties and viscosity of the hydrogel and confirm its potential application as an underwater bandage, the HPAA1 hydrogel was stretched and wrapped around the distal limb to evaluate its performance in blocking distal blood supply. Please refer to Figure 5 5C in. HPAA1 hydrogel can also adhere to the skin surface of the bent joint, proving that it will not break or peel off with joint movement. Please refer to Figure 5 5D in.

[0057] Test Example 4 Adhesion performance and release separation method: On a universal testing machine, the overlap test and standard 180° peel test were used to evaluate the tissue adhesion performance of the hydrogel. The biological tissue (i.e., pig skin, heart, stomach, liver) was cut into regular shapes (50×20×3mm) and first washed with PBS buffer. Two substrate samples (tissue / tissue) were adhered in the middle with hydrogel (15×15×1mm). The overlap shear test and standard 180° peel test were performed at room temperature with a tensile rate of 100mm / min until failure. The stress-displacement curve in the overlap test was recorded, and the shear stress was calculated using the formula: , where F max1 is the maximum force of the lap shear test, W and L represent the width and length of the hydrogel sample. The force / width-displacement curve in the 180° peel test was recorded, and the interface toughness was calculated using the formula: Interface toughness = F max / W, where F max is the maximum force in the 180° peel test, and W represents the width of the hydrogel sample.

[0058] First, HPAA and HAAA were adhered to wet pig skin to observe their adhesion properties. The results showed that the shear stress values ​​of HAAA1, HAAA2, HPAA1 and HPAA2 were 15.42kPa, 21.95kPa, 159.8kPa and 115.9kPa, respectively, and the interface toughness values ​​were 96.94N / m, 56.68N / m, 750.19N / m and 406.23N / m, respectively. Please refer to Figure 6 6A to 6F in the.

[0059] Comparing the HPAA patch and the borate-free HAAA patch can show the effect of the phenyl boronate bond on the adhesion properties. The results showed that HPAA1 had the strongest adhesion. Due to the presence of the boronate bond, the adhesion strength of the HPAA patch to wet pig skin was significantly higher than that of the HAAA patch. In addition, the adhesion strength of the HPAA1 hydrogel on wet pig skin was significantly higher than that of HPAA2, which may be due to the higher hardness of HPAA2, which reduces its adhesion properties. To demonstrate the adhesion of the hydrogel patch underwater, the pig skin was placed in a petri dish filled with water, and then the patch was gently placed on the pig skin. After waiting for 2 seconds, the hydrogel tissue was lifted with tweezers to observe its adhesion properties. Without the need to apply pressure, the HPAA1 patch was able to adhere to the surface of the pig skin underwater and stably lift nearly 100 times the pig skin, please refer to Figure 6 This enhancement is due to the presence of phenylboronic acid ester bonds, which, upon contact with tissue, break the water film by self-lysis, absorb interfacial water, and then react with amino groups on the tissue surface. Please refer to Figure 6 6H in.

[0060] In addition, the hydrogel is also detachable. Two identical skin incisions were made on the back of rats, and the HPAA1 patch was used for wound treatment. Cotton balls containing saline or 20% glucose solution were covered on the surface of the hydrogel for a detachability test, and the detachability of the hydrogel was observed after 20 minutes.

[0061] The results showed that the use of 20% glucose solution can be used for painless and non-invasive separation within 20 minutes without causing any significant adverse effects on the wound. Figure 6 The glucose solution is pH neutral and will not irritate the wound, and sterile glucose solution is easily available in clinical practice. The on-demand detachability of the HPAA1 patch also solves a key problem in wound management.

[0062] In addition, HPAA1 was adhered to a series of representative wet organ tissues (heart, liver, spleen, lung, kidney) and other materials (iron, rubber, plastic, glass, polytetrafluoroethylene) to observe its adhesion properties.

[0063] The experimental results show that the hydrogel exhibits moderate adhesion to various non-biological materials such as metal, rubber, plastic, glass, etc., but has almost no obvious adhesion to polytetrafluoroethylene. Please refer to Figure 7 7A in the animal organ adhesion experiments showed that the HPAA1 patch showed the strongest adhesion to various wet tissues compared with the control group. Please refer to Figure 7 7B to 7H in.

[0064] Test Example 5 Cells and animals: L929 cell line was obtained from KeyGENBioTECH (Nanjing, China). SD rats (female, 180–220 g) were obtained from the Animal Center of Southern Medical University and acclimated in the laboratory for one week before the experiment. Animals had free access to food and water. Animal experiments were approved by the Institutional Animal Care and Use Committee of Zhujiang Hospital (ethics number LAEC-2024-209).

[0065] Biocompatibility: The in vitro biocompatibility of HPAA1 hydrogel with L929 fibroblasts was evaluated by live / dead cell assay. Live / dead cell staining showed that almost no cell death was observed in the HPAA1 and HPAA2 groups within 2 days compared with the control group. Please refer to Figure 8 8A and 8B in.

[0066] HPAA1 samples (5 mm in diameter and 1 mm in thickness) were implanted into the back of SD rats to evaluate the in vivo biocompatibility test. On the 28th day, tissue samples of the heart, liver, spleen, lung, kidney, and skin were collected and stained with hematoxylin-eosin (HE). The results showed that after 28 days, there was mild fibrosis in the subcutaneous tissue near the implant. Further evaluation of the main organs of the rats (heart, liver, spleen, lung, and kidney) did not reveal obvious histological reactions or pathological changes. Please refer to Figure 8 8F in the.

[0067] Test Example 6 Degradation behavior of hydrogels: Hydrogels were degraded in vivo and in vitro. HPAA1 samples in the swelling equilibrium state were placed in 10 mL PBS (pH = 7.4) (in vitro experiments) or on the back of SD rats (in vivo experiments). Hydrogel samples were harvested and dried on days 0, 7, 14, 21, and 28 in each group.

[0068] The results showed that the HPAA hydrogel gradually degraded over time in vitro. When placed in PBS at 37°C, the weight of the hydrogel decreased by more than 40% after 28 days.

[0069] Furthermore, in vivo experiments showed a similar degradation pattern to that observed in vitro, with a weight loss of more than 40% within 28 days, see Figure 8 8C to 8E in.

[0070] Test Example 7 Evaluation of wound closure in vivo: The skin injury model was constructed by making four 2 cm incisions on the back of rats. The wounds were closed with sutures, cyanoacrylate (biological tissue glue, Beijing Ji Tian Biotechnology) and HPAA1. The other group was a blank group. Please refer to Fig. 9 9A in Figure 9. Wound images were taken on days 0, 1, 3, 7, 10, and 14.

[0071] The results showed that the HPAA1 patch showed stronger mechanical strength than the control group, and could adhere to the skin surface to close the incision even under external forces such as pulling and twisting. From the 7th day when the patch was detached with glucose solution until the end of observation, the HPAA1 group did not experience wound tearing similar to the cyanoacrylate treatment group, please refer to Fig. 9 9B in it.

[0072] Wound skin tissues were collected on days 7 and 14 and stained with HE and Masson's trichrome. Images were taken with 3D HISTECH panoramic scanning. Re-epithelialization and collagen formation were evaluated using ImageJ software.

[0073] Results showed that wounds treated with HPAA1 had significantly smaller scars and less inflammation at days 7 and 14 compared to the control group. Collagen deposition in the wounds was assessed by Masson staining, and the HPAA1-treated group showed denser and more regular collagen fibers, similar to the reticular pattern of healthy dermis. At day 14, the HPAA1 group also showed better structural healing, such as a thinner epithelial layer, more hair follicles and subcutaneous glands, see Fig.10 10A to 10C.

[0074] IF staining was used to detect the expression of CD31 and α-SMA, and 3DHISTECH panoramic scanning was used to collect IF staining images. Compared with other groups, the CD31 vascular density of wounds treated with HPAA1 was lower on days 7 and 14. Due to the tensile resistance of the patch, the wound area of ​​the HPAA1-treated wound was smaller and no granulation tissue was formed. Please refer to Fig.10 10D and 10E in.

[0075] In addition, in HPAA1-treated wounds, the expression of α-SMA was significantly decreased on day 7 and then significantly increased on day 14. Fig.10 Figure 10D and 10F. The results show that pressure applied by the HPAA patch inhibits the expression of early myofibroblasts and prevents the formation of disordered collagen fibers. After removal of the HPAA1 patch, activation of myofibroblasts promotes proper collagen deposition.

[0076] In summary, the regulated expression of CD31 and α-SMA in the HPAA1-treated group more effectively inhibited scar formation and promoted the restoration of normal skin structure.

[0077] Test Case 8 In vivo hemostatic property: The rat liver incision model, tail amputation model and cardiac puncture model were used to evaluate the hemostatic property of the hydrogel.

[0078] The rat liver incision model was constructed by making a 5 mm wound on the liver and then covering the wound with an HPAA patch (8 × 8 × 0.2 mm). Please refer to Fig.11 The HPAA1 patch adheres directly to the wound within 1-2 seconds after contact without applying pressure, please refer to Fig.11 11B in. Compared with the control group, the HPAA1-treated group had a shorter hemostatic time and stronger hemostatic ability. Please refer to Fig.11 The quantitative results showed that the total blood loss in the HPAA1 group (about 0.06g) was significantly lower than that in the sponge group (about 0.3g) and the blank group (about 0.9g). Fig.11 11D in. On the second day after surgery, liver tissue sections were histologically analyzed. The patch in the HPAA1-treated group had fallen off, and the liver tissue regenerated and filled the gap. No adverse peritoneal adhesion or inflammatory response was observed. Please refer to Fig.11 11E in.

[0079] The rat tail amputation model was constructed by cutting the middle of the mouse tail with surgical scissors, and then the HPAA1 patch (8×8×0.2mm) was attached to the wound. Please refer to Fig.11 Compared with the control group, the HPAA1 patch quickly wrapped the severed tail and significantly reduced bleeding. Fig.11 The quantitative results showed that the total blood loss in the HPAA1 group (about 0.05g) was much lower than that in the sponge group (about 0.3g) and the blank group (about 0.9g). Please refer to Fig.11 11H in.

[0080] In addition, the rat cardiac puncture wound model was established by cardiac puncture wound (2 mm in diameter). HPAA1 patch (8 × 8 × 0.2 mm) was immediately adhered to the bleeding site, please refer to Fig.11 The results showed that application of the HPAA1 patch to the epicardial surface of a beating rat heart rapidly stopped bleeding, see Fig.11 11J in.

[0081] In summary, the HPAA1 patch effectively sealed the bleeding site and allowed the wound to pass through the bleeding phase. The wound then achieved hemostasis through natural coagulation.

[0082] Test Example 9 HPAA1 was used to evaluate the sealing of damaged lung lobes. HPAA1 was used to treat lacerations (1 cm) of porcine lung lobes to observe air leakage of the lobes in a water bath. The results showed that the damaged lung lobes could be quickly repaired by the HPAA1 patch (3×1.5×0.5 cm) within 1-2 seconds. The sealed porcine lung lobes were subjected to a continuous inflation-deflation cycle, and the HPAA patch could seal for more than 6 hours. Please refer to Fig.12 12A in.

[0083] To evaluate the sealing ability of HPAA1 on damaged hearts, HPAA1 was used to treat puncture wounds (1 cm) in pig hearts to observe fluid leakage from the heart. The results showed that the damaged heart could be quickly repaired by the HPAA1 patch (3×1.5×0.5 cm) within 1-2 seconds, and the sealed pig heart could be stored at room temperature for more than 6 hours. Please refer to Fig.12 12B in.

[0084] To evaluate the sealing ability of HPAA1 on damaged stomach, HPAA1 was used to treat a circular perforation wound (1 cm in diameter) in a pig stomach to observe the leakage of gastric fluid. The hole was quickly repaired by an HPAA1 patch (3×1.5×0.5 cm) within 1-2 seconds. The sealed pig stomach could be stored at room temperature for 6 hours. Please refer to Fig.12 These in vitro models demonstrate the potential of the HPAA1 patch to immediately seal air and fluid leaks in organs.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a hydrogel hemostatic patch with underwater adhesion, characterized in that: The preparation method of the patch comprises: mixing hyaluronic acid modified by o-aminophenylboronic acid, acetylated beta-cyclodextrin, acrylic acid, alpha-ketoglutaric acid and water to prepare a HPAA hydrogel precursor solution; adding the hydrogel precursor solution into a mold and irradiating it with ultraviolet light to obtain the patch.

2. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 1, characterized in that: The weight ratio of the o-aminophenylboronic acid modified hyaluronic acid, acetylated β-cyclodextrin, acrylic acid, α-ketoglutaric acid and water is (13-17): (9-11): (140-160): (0.5-1.5): (300-350).

3. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 1, characterized in that: The wavelength of the ultraviolet light is 360-370 nm, and the irradiation time is 9-11 min.

4. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 1, characterized in that: The preparation method of the o-aminophenylboronic acid modified hyaluronic acid comprises: dissolving hyaluronic acid in deionized water, sequentially adding N-hydroxysuccinimide and 1-(3-dimethylpropyl)-3-ethylcarbodiimide for mixed reaction, then adding 2-aminophenylborate hydrochloride to obtain a mixed solution, adjusting the pH of the mixed solution to 4-5 for reaction, then adjusting the pH to 7.5-8.5 to stop the reaction, then dialyzing, freezing and freezing, and then placing in a freeze dryer for freeze drying to obtain the obtained solution.

5. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 4, characterized in that: The weight ratios of the hyaluronic acid, deionized water, N-hydroxysuccinimide, 1-(3-dimethylpropyl)-3-ethylcarbodiimide and 2-aminophenylborate hydrochloride are (8-12):(180-220):(6-8):(10-14):(4-6).

6. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 4, characterized in that: The pH is adjusted by adding 0.8-1.2 M sodium hydroxide aqueous solution. When the pH is 4-5, the reaction needs to be stirred at room temperature for 11-13 hours.

7. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 4, characterized in that: The dialysis step comprises: using a dialysis bag with a molecular weight cut-off MWCO: 3000-4000Da, dialysis with a sodium chloride aqueous solution containing a mass concentration of 0.8-1% for 46-50 hours, and then further dialysis with deionized water for 22-26 hours.

8. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 1, characterized in that: The preparation method of acetylated β-cyclodextrin comprises: dissolving β-cyclodextrin and triethylamine in anhydrous N,N-dimethylformamide, stirring and reacting at 250-350 r / min for 0.8-1.2 h at 0-1° C. and under nitrogen protection, then adding acryloyl chloride and stirring and reacting at 250-350 r / min for 10-14 h at room temperature, filtering and precipitating, washing, redissolving in deionized water, freezing and freezing, and then putting into a freeze dryer for freeze drying to obtain a sponge-like product.

9. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 8, characterized in that: The weight ratio of the β-cyclodextrin, triethylamine, anhydrous N,N-dimethylformamide and acryloyl chloride is (8-12): (6-8): (55-66): (4-8).

10. The method for preparing a hydrogel hemostatic patch with underwater adhesion according to claim 8, characterized in that: The method for washing the precipitate is to use ethyl acetate for precipitation, add ethyl acetate in an amount of more than 50 times the volume of the precipitate, and filter and wash for more than three times.

Citation Information

Patent Citations

  • Preparation method of culture medium mediated cross-linked hyaluronic acid-based double-cross-linked hydrogel

    CN112062981A

  • Self-adhesive hemostatic repair gel containing multi-scale pore network, and preparation method and application thereof

    CN115746388A

  • Temperature-sensitive self-shaping stretchable hyaluronic acid / beta-cyclodextrin hydrogel as well as preparation method and application thereof

    CN115850735A

  • Photo-thermal and photodynamic antibacterial hydrogel with pH / glucose dual-responsive drug release as well as preparation method and application of photo-thermal and photodynamic antibacterial hydrogel

    CN116474161A

  • Tissue sealant patch and preparation method thereof

    CN118542964A